Dual-phase sensing for early detection of prepreg structural failures via etched cladding Bragg grating - Hassan, M.R.A.; Tamchek, N.; Abas, A.F.; Johar, R.M.; Adikan, Faisal Rafiq Mahamd (Elsevier, 2011)
A dual-phase optical fiber-based sensor for early detection against prepreg structural failures is proposed and successfully demonstrated. The sensor consists of an etched fiber Bragg grating (FBG) mounted onto an aluminium plate. The sensor is tested using a simple pressure and petrochemical test rig. By observing the shift of the reflected wavelength of the FBG sensor we can simultaneously detect two parameters: (i) pressure and (ii) petrochemical. The experimental results show the potential of using the FBG sensor for early detection of submarine oil pipe leaking. (C) 2011 Elsevier B.V. All rights reserved.